A DATA-DRIVEN ANALYSIS ON THE GLOBAL VACCINATION COVERAGE - IVY SYZLYNDA NASHION, NASHION (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Many of the existing data visualization tools are using PHP or other plug-ins to generate a graphical data representation. The purpose of data visualization is to help data analyst to understand better on what the behavior of the datasets .Therefore, a free statistical language R as a platform is proposed. The objective of data visualization for the vaccination coverage is to provide a better insight on how the vaccination coverage growth. The data visualization help data analyst to easily discover the changes in behavior of datasets and how the parameters related to each other. This data visualization process is using the powerful R statistical to generate graphical output such as line plotting, scatter plot and median quartile range plotting. To carry out this research, a research-based methodology was used. It consist of five phases that is data collection, problem identification, solution implementation, analysis of solution and problem reporting. The solution will show the variations of vaccination coverage across countries by using data visualization tools in R, the association between socioeconomic/demographic factors and vaccination coverage using clustering techniques and an explanatory analysis of the global immunization programs.